Language as key for success in education? A case study of reproduction of educational inequality in everyday school life - Krompàk, Edina (Swiss Journal of Educational Research, 2018)
This ethnographic study explores the period of transition from kindergarten to primary school with a sample of multilingual children. Analyses of the education policy frames, documents and practices are used to reconstruct the selection process, as well as the production process of educational inequality on the micro level of everyday school life. Contextual frame conditions of educational policy are also conceptualized.